Jamaica : Fifth Review Under the Stand-By Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This first review under the Stand-By Arrangement (SBA) highlights that the economy has expanded for the past 15 quarters, unemployment is at historic lows, international reserve coverage is consistently high, inflation is subdued-albeit below the Bank of Jamaica (BOJ) target 4-6 percent range, the stock market was the globe's best performer in 2018, and Fitch recently upgraded Jamaica's credit rating. A slow pick-up in private investment, however, is still pointing to the need to reinvigorate the effort to remove supply-side impediments to growth and job creation. It has been observed that sustained reduction in the public wage bill will require a fundamental transformation of the compensation framework and the public sector. Moreover, the BOJ's recent advances in communication should continue to stress the central bank's commitment to its inflation mandate. The discussions described that an escalation in crime could further curtail private investment and growth. Weaker world growth and tighter global financial conditions represent important downside risks.